Technological characteristics of sugar cane under application of doses the vinasse in Rhodic Hapludox - Prado, Eber Augusto Ferreira do; Vitorino, Antonio Carlos Tadeu; Mauad, Munir; Ensinas, Simone Candido; Paim, Leandro Ramão (Revista de Ciências Agroveterinárias, 2018)
One of the main by-products of the sugar and alcohol industry is the vinasse which is rich in nutrients, especially potassium. The objective of this study was to evaluate the quality of the technological characteristics and productivity of sugarcane after application of vinasse doses in the third cut cane. The study was conducted in Rhodic Hapludox sandy clay soil, in Monte Verde plant - Bunge in county Ponta Porã, MS. A randomized block design was used, four vinasse doses (0, 450, 600 and 750 m3 ha-1) with five repetitions were evaluated. sugarcane variety RB 855453 early cycle was used, with line spacing of 1.5 m. The planting of cane occurred in 2008, using conventional tillage. The POL% increased 3.38%, for the °BRIX%, there was an increase of 5.03%, the AR% increased 22%, for the variable FIBER%, there was a 6.7% e the ATR% increased 4.94%, with vinasse doses. For productivity, there was an increase of 4 Mg from the lowest to the highest dose of vinasse. The application of vinasse doses improved the quality of the raw material, except for industry purity. The vinasse doses increased the productivity of sugarcane.